Tissue Salvage in the Non-reperfused Myocardium Mediated by (the absence of the circadian rhythm gene) mPer2 and (the receptor tyrosine kinase) EphrinA1 - Dries, Jessica L. (East Carolina University, 2010)
Alterations in circadian rhythm have been associated with numerous cardiovascular pathologies. In project 1, we tested the hypothesis that functional mutation of the Per2 circadian clock gene would provide cardioprotection to mice that had undergone permanent coronary ligation to induce myocardial infarction (MI). mPer2-M mice had a 43% smaller infarct size compared to wild type (WT), along with reduced leukocyte infiltration, increased capillary density, increased myocyte hypertrophy, and reduced myocyte apoptosis. This suggests that mutation of mPer2 is cardioprotective.  The heart lacks a sufficient capacity for endogenous repair after injury. We tested the hypothesis that intramyocardial administration of ephrinA1-Fc at the time of MI would promote cardiomyocyte survival, subsequently reducing infarct size and inflammatory cell infiltrate. The ephrinA1 ligand has been predominantly characterized as a pro-angiogenic factor in development and tumor progression, but is also involved in apoptosis and inflammation. The ephrinA1 ligand has not been studied in the adult myocardium or in the context of acute MI.   Intramyocardial injection of EphrinA1-Fc reduced infarct size, necrosis, chamber dilation, and left ventricular free wall thinning four days after MI. Inflammation was also substantially reduced, with reductions in neutrophil and leukocyte density. We measured reductions in serum cTnI, and cleaved PARP, and increased bag-1 protein expression, suggesting reduced cell death. Phosphorylated AKT/total AKT protein was increased, indicating improved cellular survival. Our analysis of gene expression revealed that Eph receptors A1-A4, A6, and A7 were expressed in the uninjured adult myocardium. Expression of EphA1-A3 and EphA7 was significantly increased following MI while EphA6 expression was decreased. Treatment with ephrinA1-Fc further increased EphA1 and EphA2 gene expression, and also increased EphA4 expression.   To date, only reperfusion has been shown to reduce injury and improve long-term remodeling. We have discovered two new mechanisms by which this can be effected: 1) we have observed a dramatic reduction in cardiac injury in mice lacking a functional circadian gene product mPer2; and 2) we are the first to identify a role for ephrinA1/EphA signaling in the repair process following MI, and have identified a novel, protective role for ephrinA1-Fc administration at the time of MI.
Keywords: Biology, Physiology; Cardiovascular Diseases--therapy; Models, Animal; Physiology